Physico-chemical Analysis Of High Fibre Cereal Bar Formulated With Glutinous Rice Flakes And Sunnah Foods - Agbaje Rafiu; Chek Zaini Hassan; Abdul Rahman Asma; Norlelawati Arifin (International Knowledge Press, 2024)
Journal of Advances in Food Science & Technology 2(2):47-58, 2015 International Knowledge Press www.ikpress.org